Polymer therapeutics with a coiled coil motif targeted against murine bcl1 leukemia - Pola, Robert; Laga, Richard; Ulbrich, Karel; Sieglová, Irena; Král, Vlastimil; Fábry, Milan; Kabešová, Martina; Kovář, Marek; Pechar, Michal (Biomacromolecules, 2013)
The specificity of polymer conjugates based on N-(2-hydroxypropyl)methacrylamide (HPMA) bearing cytostatic drugs for cancer cells could be significantly increased by the incorporation of a suitable targeting ligand, such as a monoclonal antibody (mAb). However, direct binding of the protein to the polymer carrier could cause considerable problems, such as decreasing the binding capacity of mAb to its target. Here, we introduce a novel strategy of joining a targeting moiety to a polymeric conjugate with cytostatic drug. The scFv of B1 mAb (specific for BCL1 leukemia cells) was tagged with peptide K ((VAALKEK)4). Peptide E ((VAALEKE)4), which forms a stable coiled coil structure heterodimer with peptide K, was assembled with the HPMA copolymers bearing doxorubicin. Such targeted polymeric conjugates possess very selective and high binding activity toward BCL1 cells. Similarly, targeted polymeric conjugates exert approximately 100 times higher cytostatic activity toward BCL1 cells in comparison to nontargeted conjugates in vitro. At the same time, the conjugates have comparable and rather low cytostatic activity for 38C13 cells, which are used as a negative control, in vitro.
Keywords: doxorubicin; cytostatické látky; Recombinant Fusion Proteins; monoklonální protilátky; leukemie; protinádorová antibiotika; Cell Line, Tumor; Cell Proliferation; Acrylamides; myši inbrední BALB C; methakryláty; rekombinantní fúzní proteiny; Drug Carriers; Polymers; Mice, Inbred BALB C; Leukemia; Animals; biokompatibilní materiály; polymery; zvířata; Antibiotics, Antineoplastic; akrylamidy; myši; proliferace buněk; Antibodies, Monoclonal; Cytostatic Agents; nádorové buněčné linie; Mice; nosiče léků; Methacrylates; Biocompatible Materials; Doxorubicin